Ambivalent identities emerging in transnational migrations between Argentina and Slovenia - Repič, Jaka (Two Homelands, 2010)
The article explores the issue of ambivalent identities in transnational migrations between Argentina and Slovenia. Recent migrations between the two states are historically and causally related to political emigration after the Second World War from Slovenia to Argentina and the formation of a diasporic community that asserted complex symbolic links to its homeland. Due to this connection, contemporary migrants can claim and (re)activate their Slovene origin, ‘original’ culture, belonging, citizenship and social identities.